Cannabinoid‐1 receptor antagonist rimonabant (SR141716) increases striatal dopamine D2 receptor availability. (29th September 2011) - Crunelle, Cleo L.; van de Giessen, Elsmarieke; Schulz, Sybille; Vanderschuren, Louk J. M. J.; de Bruin, Kora; van den Brink, Wim; Booij, Jan
ABSTRACT The cannabinoid 1 receptor antagonist rimonabant (SR141716) alters rewarding properties and intake of food and drugs. Additionally, striatal dopamine D2 receptor (DRD2) availability has been implicated in reward function. This study shows that chronic treatment of rats with rimonabant (1.0 and 3.0 mg/kg/day) dose‐dependently increased DRD2 availability in the dorsal striatum (14 and 23%) compared with vehicle. High‐dose rimonabant also increased DRD2 availability in the ventral striatum (12%) and reduced weight gain. Thus, up‐regulation of striatal DRD2 by chronic rimonabant administration may be an underlying mechanism of action and confirms the interactions of the endocannabinoid and dopaminergic systems.